Public expenditures, growth, and poverty: Lessons from developing countries - Fan, Shenggen (International Food Policy Research Institute, 2008)
More than 1 billion people around the globe still live on less than U.S. $1 a day as measured in purchasing power parity in 2001. Over the past 20 years, rapid economic growth in East Asia has reduced the total number of poor people from 800 million in 1981 to 270 million in 2001. In South Asia, during the same period the total number of poor people declined only marginally, from 480 million to 430 million. However, poverty rates did not fall in Africa, Latin America, or the Middle East, and the rate of economic growth was far lower during this period than it was 20 years ago. In fact, the number of the poor in Sub- Saharan Africa has almost doubled, from 160 million in 1981 to more than 300 million in 2001 (Chen and Ravallion 2004). Using the poverty line measured at U.S. $2 per day, the world's total poor increased from 2.5 billion in 1981 to more than 2.7 billion in 2001, and the associated poverty rate fell from 67 percent to 53 percent, which represents a much slower rate than the drop in the U.S. $1 per day poverty rate. It is obvious, therefore, that a "business as usual" approach is wholly inadequate. Instead, a more effective poverty alleviation strategy is urgently required in recognition of the fact that persistent poverty and malnutrition result in irreversible costs to human and economic development.